Design Thinking–Informed Simulation: An Innovative Framework to Test, Evaluate, and Modify New Clinical Infrastructure. Issue 3 (June 2020) - Petrosoniak, Andrew; Hicks, Christopher; Barratt, Lee; Gascon, Dominic; Kokoski, Candis; Campbell, Doug; White, Kari; Bandiera, Glen; Lum-Kwong, Margaret Moy; Nemoy, Lori; Brydges, Ryan
Abstract : Introduction: Designing new healthcare facilities is complex and transitions to new clinical environments carry high risks, as unanticipated problems may arise resulting in inefficient care and patient harm. Design thinking, a human-centered design method, represents a unique framework to support the planning, testing, and evaluation of new clinical spaces throughout all phases of construction. Healthcare simulation has been used to test new clinical spaces, yet most report using simulation only in the late design stages. Moreover, healthcare design models have potentially underused human factors approaches calling for human-centered design. We applied a multimodal simulation-based approach underpinned by the principles of design thinking throughout the planning and construction stages of a newly renovated academic emergency department. Methods: A multidisciplinary team developed and integrated 3 simulation strategies (table-top, mock-up, and in situ simulation) into the 5-step process of design thinking. Through end-user engagement, we identified potential challenges, prototyped solutions through table-top and mock-up simulations, and iteratively tested these solutions through in situ simulation within the actual clinical space. Results: The team used end-user engagement and feedback to brainstorm and implement effective solutions to problems encountered before opening the new emergency department. The iterative steps and targeted use of simulation resulted in redesigning departmental processes and actual clinical space while mitigating anticipated safety threats and departmental deficiencies. Conclusions: Design thinking coupled with multimodal simulation across all phases of construction enhanced the design and testing of new clinical infrastructure. Applying this approach early, thoroughly, and efficiently will help healthcare organizations plan changes to clinical spaces.